A review of the finless snake eels of the genus Apterichtus (Anguilliformes: Ophichthidae), with the description of five new species - Mccosker, John E.; Hibino, Yusuke (Zootaxa, 2015)
The 18 species of finless snake eels of the genus Apterichtus (family Ophichthidae, subfamily Ophichthinae) are reviewed. Included are: A. anguiformis from the Mediterranean and eastern Atlantic; A. ansp from the Carolinas to Brazil in the western Atlantic; A. australis from South and Central Pacific islands, including Japan; A. caecus from the Mediterranean and eastern Atlantic; A. equatorialis from the eastern Pacific; A. flavicaudus from Hawaii, Midway Island, and possibly Australia and Seychelles; A. gracilis from the eastern central Atlantic; A. hatookai from Japan and China; A. kendalli from the western Atlantic and St. Helena Island; A. klazingai from South Africa to Hawaii; A. monodi from the eastern Atlantic; A. moseri from Japan; and A. orientalis from Japan. Five new species are described and illustrated: A. dunalailai from Vanuatu and Fiji at 291–450 m; A. jeffwilliamsi from Vanuatu at 4–16 m; A. malabar from New South Wales, Australia at 44–66 m; A. mysi from the Marquesas Islands at 35–64 m; and A. nariculus from Ambon Island, Indonesia at 28–30 m. A neotype is designated for Apterichtus caecus. An identification key is provided. The synonymy of the genus Apterichtus is reviewed. Apterichtus keramanus Machida, Hashimoto & Yamakawa 1997, is referred to ----------------Ichthyapus.